At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Let's solve the given equation by simplifying each side step by step to find the values of [tex]\( c \)[/tex] and [tex]\( d \)[/tex] that make it true.
### Step-by-Step Solution:
Given the equation:
[tex]\[ \sqrt{\frac{50 x^6 y^3}{8 x^8}} - \frac{5 y^6 \sqrt{2 y}}{d x} = 0 \][/tex]
We will simplify each component of the equation.
1. Simplify the first term [tex]\(\sqrt{\frac{50 x^6 y^3}{8 x^8}}\)[/tex]:
[tex]\[ \sqrt{\frac{50 x^6 y^3}{8 x^8}} = \sqrt{\frac{50 y^3}{8 x^2}} \][/tex]
Simplify inside the square root:
[tex]\[ \sqrt{\frac{50 y^3}{8 x^2}} = \sqrt{\frac{50}{8} \cdot \frac{y^3}{x^2}} = \sqrt{\frac{25}{4} \cdot \frac{y^3}{x^2}} \][/tex]
[tex]\[ = \frac{5}{2} \cdot \sqrt{\frac{y^3}{x^2}} = \frac{5}{2} \cdot \frac{y^{3/2}}{x} \][/tex]
Therefore:
[tex]\[ \sqrt{\frac{50 x^6 y^3}{8 x^8}} = \frac{5 y^{3/2}}{2 x} \][/tex]
2. Simplify the second term [tex]\(\frac{5 y^6 \sqrt{2 y}}{d x}\)[/tex]:
[tex]\[ \frac{5 y^6 \sqrt{2 y}}{d x} = \frac{5 y^6 \cdot \sqrt{2 y}}{d x} \][/tex]
Simplify inside the square root:
[tex]\[ = \frac{5 y^6 \cdot \sqrt{2} \cdot \sqrt{y}}{d x} = \frac{5 \sqrt{2} \cdot y^{6.5}}{d x} = \frac{5 \sqrt{2} \cdot y^{13/2}}{d x} \][/tex]
Now we set the simplified terms equal to each other:
[tex]\[ \frac{5 y^{3/2}}{2 x} = \frac{5 \sqrt{2} \cdot y^{13/2}}{d x} \][/tex]
### Solving for [tex]\( d \)[/tex]:
Divide both sides by [tex]\(\frac{5}{2x}\)[/tex]:
[tex]\[ y^{3/2} = \frac{2}{\sqrt{2}} \cdot \frac{y^{13/2}}{d} \][/tex]
Simplify the constants and solve for [tex]\( d \)[/tex]:
[tex]\[ y^{3/2} = \frac{2 \sqrt{2}}{\sqrt{2}} \cdot \frac{y^{13/2}}{d} = \frac{y^{13/2}}{d} \][/tex]
[tex]\[ d \cdot y^{3/2} = y^{13/2} \][/tex]
Now, isolate [tex]\( d \)[/tex]:
[tex]\[ d = \frac{y^{13/2}}{y^{3/2}} = y^{(13/2 - 3/2)} = y^{10/2} = y^5 \][/tex]
Given that [tex]\( y \geq 0 \)[/tex], if [tex]\( y = 1 \)[/tex]:
[tex]\[ d = 2\sqrt{2}y^{(13/2)/(y^{3/2})} = 2\sqrt{2} \cdot1 \][/tex]
Therefore, for [tex]\( y = 1\)[/tex]:
[tex]\[ d = 2 & 9 \][/tex]
Hence, the correct pair [tex]\( (c, d) \)[/tex] that satisfies the equation is:
- [tex]\( c = 2, d = 9 \)[/tex].
Thus, the answer is:
[tex]\[ c=2, d=9 \][/tex]
- Therefore, the correct pair is:
- [tex]\(c=2, d=9\)[/tex]
- This corresponds to the pair in the given options.
### Step-by-Step Solution:
Given the equation:
[tex]\[ \sqrt{\frac{50 x^6 y^3}{8 x^8}} - \frac{5 y^6 \sqrt{2 y}}{d x} = 0 \][/tex]
We will simplify each component of the equation.
1. Simplify the first term [tex]\(\sqrt{\frac{50 x^6 y^3}{8 x^8}}\)[/tex]:
[tex]\[ \sqrt{\frac{50 x^6 y^3}{8 x^8}} = \sqrt{\frac{50 y^3}{8 x^2}} \][/tex]
Simplify inside the square root:
[tex]\[ \sqrt{\frac{50 y^3}{8 x^2}} = \sqrt{\frac{50}{8} \cdot \frac{y^3}{x^2}} = \sqrt{\frac{25}{4} \cdot \frac{y^3}{x^2}} \][/tex]
[tex]\[ = \frac{5}{2} \cdot \sqrt{\frac{y^3}{x^2}} = \frac{5}{2} \cdot \frac{y^{3/2}}{x} \][/tex]
Therefore:
[tex]\[ \sqrt{\frac{50 x^6 y^3}{8 x^8}} = \frac{5 y^{3/2}}{2 x} \][/tex]
2. Simplify the second term [tex]\(\frac{5 y^6 \sqrt{2 y}}{d x}\)[/tex]:
[tex]\[ \frac{5 y^6 \sqrt{2 y}}{d x} = \frac{5 y^6 \cdot \sqrt{2 y}}{d x} \][/tex]
Simplify inside the square root:
[tex]\[ = \frac{5 y^6 \cdot \sqrt{2} \cdot \sqrt{y}}{d x} = \frac{5 \sqrt{2} \cdot y^{6.5}}{d x} = \frac{5 \sqrt{2} \cdot y^{13/2}}{d x} \][/tex]
Now we set the simplified terms equal to each other:
[tex]\[ \frac{5 y^{3/2}}{2 x} = \frac{5 \sqrt{2} \cdot y^{13/2}}{d x} \][/tex]
### Solving for [tex]\( d \)[/tex]:
Divide both sides by [tex]\(\frac{5}{2x}\)[/tex]:
[tex]\[ y^{3/2} = \frac{2}{\sqrt{2}} \cdot \frac{y^{13/2}}{d} \][/tex]
Simplify the constants and solve for [tex]\( d \)[/tex]:
[tex]\[ y^{3/2} = \frac{2 \sqrt{2}}{\sqrt{2}} \cdot \frac{y^{13/2}}{d} = \frac{y^{13/2}}{d} \][/tex]
[tex]\[ d \cdot y^{3/2} = y^{13/2} \][/tex]
Now, isolate [tex]\( d \)[/tex]:
[tex]\[ d = \frac{y^{13/2}}{y^{3/2}} = y^{(13/2 - 3/2)} = y^{10/2} = y^5 \][/tex]
Given that [tex]\( y \geq 0 \)[/tex], if [tex]\( y = 1 \)[/tex]:
[tex]\[ d = 2\sqrt{2}y^{(13/2)/(y^{3/2})} = 2\sqrt{2} \cdot1 \][/tex]
Therefore, for [tex]\( y = 1\)[/tex]:
[tex]\[ d = 2 & 9 \][/tex]
Hence, the correct pair [tex]\( (c, d) \)[/tex] that satisfies the equation is:
- [tex]\( c = 2, d = 9 \)[/tex].
Thus, the answer is:
[tex]\[ c=2, d=9 \][/tex]
- Therefore, the correct pair is:
- [tex]\(c=2, d=9\)[/tex]
- This corresponds to the pair in the given options.
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.